Investment analysis for determining toll fee of gas distribution pipeline in bekasi fajar industrial estate - Muthiasari Pertiwi, Hedia; P. K. Bintoro, Bambang (The Indonesian Journal of Business Administration, 2018)
Abstract – In an effort to maintain energy sufficiency in Indonesia, PT Pertamina Gas is currently facing a request from PT Persada Agung Energi to distribute gas to Lippo Cikarang for the next 9 years. In which previously, this cooperation requires the development of gas distribution pipeline in Bekasi Fajar Industrial Estate. So in this regard, a financial feasibility analysis needs to be conducted to assess this investment and determine the toll fee as the revenue source for PT Pertamina Gas and the distribution tariff for PT Persada Agung Energi in using the pipeline. It will be performed by using consideration of capital budgeting techniques and the Minister of Energy and Natural Resources Regulation No. 58 Year 2017, which set the maximum internal rate of return at 11%. Then, with a hurdle rate of 10.5%, it turns out that the toll fee of $ 0.11085 per MSCFD and investment cost of $ 375,132.40 can yield a net present value of $ 8,945.02, discounted payback period of 8.78, and profitability index of 1.27. In addition, the risk assessment performed is deemed to be measurable and can be tolerated by PT Pertamina Gas. So financially, this pipeline investment is considered feasible to conduct.Keywords: distribution pipeline, financial feasibility study, gas infrastructure, investment analysis